2021
DOI: 10.5498/wjp.v11.i7.297
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and depression: Reflecting a deepening knowledge of the gut and brain effects of a ubiquitous molecule

Abstract: The versatility of glutamate as the brain’s foremost excitatory neurotransmitter and modulator of neurotransmission and function is considered common knowledge. Years of research have continued to uncover glutamate’s effects and roles in several neurological and neuropsychiatric disorders, including depression. It had been considered that a deeper understanding of the roles of glutamate in depression might open a new door to understanding the pathological basis of the disorder, improve the approach to patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 140 publications
1
22
0
Order By: Relevance
“…Changes in the metabolism of neurotransmitters have been widely associated with depressive psychopathology [ 70 72 ]. The neurotransmitters more affected by inflammation are serotonin, dopamine, and glutamate, with alterations in their synthesis, release, and reuptake.…”
Section: Neurobiology Of Post-covid-19 Depressive Symptomsmentioning
confidence: 99%
“…Changes in the metabolism of neurotransmitters have been widely associated with depressive psychopathology [ 70 72 ]. The neurotransmitters more affected by inflammation are serotonin, dopamine, and glutamate, with alterations in their synthesis, release, and reuptake.…”
Section: Neurobiology Of Post-covid-19 Depressive Symptomsmentioning
confidence: 99%
“…A brief introduction Schizophrenia is a significant cause of disability with varied causes, and gut microbiome has been linked to its development [45][46][47][48][49][50] Depression is a prevalent cause of disability worldwide, with the gut microbiome being implicated in its pathogenesis [60][61][62] Generalized anxiety disorder (GAD) is a prevalent and enduring type of anxiety, affecting 4%-6% of the total population [70] Autism spectrum disorder (ASD) is a neurodevelopmental condition that affects social interaction and communication and is typically identified in early childhood [1,5,77,78] Neurotransmitters involved in the mental disorders Impairment in the tryptophan to serotonin conversion pathway is plausibly linked to schizophrenia [9] Researchers suggest that d-serine could be associated with schizophrenia [54,57] The role of GABAergic transmission in schizophrenia has recently risen in significance [54] Tryptophan and Serotonin are centrally involved in the pathogenesis of depression [9] Modifying dopamine levels may have therapeutic applications for depression [21] GABA has been associated with treating depression [31] Glutamatergic signaling has been linked to depression [42,44] Tryptophan and serotonin also play a crucial role in the pathogenesis of anxiety [9] Modifying dopamine levels can have therapeutic applications for anxiety [21] GABA can also reduce anxiety [31] Modifying dopamine levels can have therapeutic applications on autism [21] Glutamate metabolization may be linked to autism [38,42] Microbiota effect on the neurotransmitters -Numerous bacterial species have reportedly expressed serotonin-synthesizing properties [14] -Gut commensal strains Lactobacillus and Bifidobacterium have been found able to produce GABA [54] -Altering gut microbial may modify the metabolism of d-amino acids…”
Section: Schizophrenia Depression Anxiety Disorder Autism Spectrum Di...mentioning
confidence: 99%
“…In another meta-analysis, Luykx et al [ 27 ] also noted region- and state-specific alterations in concentrations of glutamate and glutamine, an essential amino acid that is a result of glutamate conversion, in depression. The importance of glutamatergic neurotransmission in depression is also based on studies that showed altered glutamine concentrations despite normal glutamate levels [ 28 , 29 ].…”
Section: Glutamatergic Hypothesis Of Depressionmentioning
confidence: 99%
“…These patients have significantly elevated glutamate levels in the blood and CSF compared to non-affected individuals, and the intraparenchymal-blood glutamate concentration gradient also becomes extremely high. Similarly, a recent study has proposed a connection between the gut–brain axis and glutamate that can contribute to the development of depression during gut–brain dysfunction [ 28 ].…”
Section: The Imbalance Of Blood-glutamate Concentration Gradient Foll...mentioning
confidence: 99%